Risk of bone fracture by using dipeptidyl peptidase-4 inhibitors, glucagon-like peptide-1 receptor agonists, or sodium-glucose cotransporter-2 inhibitors in patients with type 2 diabetes mellitus: a network meta-analysis of population-based cohort studies - Mostafa, Mohamed E. A.; Alrasheed, Tariq (Frontiers in Endocrinology, 2024)
Background: Type 2 diabetes mellitus (T2DM) is linked to a heightened likelihood of experiencing fractures. It is crucial to ascertain whether medications used to lower blood sugar levels can elevate the risk of fractures. We aimed to investigate and compare the effects of glucagon-like peptide 1 receptor agonists (GLP-1RA), Dipeptidyl Peptidase-4 Inhibitors (DPP-4i), and Sodium-Glucose Cotransporter-2 Inhibitors (SGLT-2i) on the fracture risk in patients with T2D in the real world. Methods: A network meta-analysis conducted an inclusive literature search in PubMed, Scopus, Web of Science, and Cochrane Library to select appropriate population-based cohort studies that investigated the risk of bone fractures of (GLP-1RA), (DPP-4i) or (SGLT-2i) in the real world. A network meta-analysis (NMA) was performed using R software to investigate the risk of total fractures as a primary outcome among patients who used (GLP-1RAs), (SGLT-2i) or (DPP-4i) versus each other or other glucose-lowering medications (GLMs). The odds ratio (OR) and 95% confidence interval (CI) were summarized overall network and for each pairwise direct and indirect comparison. The surface under the cumulative ranking curve (SUCRA) with the Pscores was calculated for each treatment in the network meta-analysis to detect their cumulative ranking probabilities in lowering the risk of total fractures. Results: In our NMA, we identified a set of 13 population-based cohort studies comprising a total of 1,064,952 patients. The risk of fracture was identified with the follow-up duration for each class. We found a significant decrease in the fracture risk by about 87% associated with patients who used SGLT2 inhibitors in combination with other glucose-lowering medications, followed by SGLT2 inhibitors alone by about 67%, then GLP-1 receptor agonists by about 60%, and at last DPP-4 inhibitors by about 55%. Conclusion: Our study's collective findings suggest a significant association of the low risk of fracture with the use of SGLT2i with other GLMs combination, SGLT2i alone, GLP-1RA, and DPP-4i, respectively. This population-based analysis offers the best available evidence and might be helpful for clinicians in the decision of the most suitable T2DM treatment strategies, especially for elderly type 2 diabetic patients, as they may be safe in terms of fracture.